Cadmium telluride quantum dot-exposed human bronchial epithelial cells: a further study of the cellular response by proteomics. Issue 6 (18th November 2019) - Xu, Yan-Ming; Tan, Heng Wee; Zheng, Wei; Liang, Zhan-Ling; Yu, Fei-Yuan; Wu, Dan-Dan; Yao, Yue; Zhong, Qiu-Hua; Yan, Rui; Lau, Andy T. Y.
Graphical Abstract: Abstract: Quantum dots (QDs) are luminescent nanoparticles with superior versatility. In this regard, cadmium telluride (CdTe) QDs have been widely used for various bioimaging applications. Although these nano-Cd containing particles can be capped with shells to reduce their cytotoxicity, these shells would be gradually disintegrated after a certain period of time, thereby inevitably exerting nanotoxicity. Previously, we showed that treatment of human bronchial epithelial BEAS-2B cells with uncapped CdTe QDs (520Q, 580Q and 730Q with emission maximum at 520, 580 and 730 nm, respectively) elicited dose-dependent cytotoxicity for 520Q and 580Q (<5 nm), while 730Q (>5 nm) elicited negligible cytotoxicity. In order to gain a more global perspective on the action mechanism of these nano-Cd particles, here, we further characterized the proteome response of BEAS-2B when challenged with the above QDs. Interestingly, among the three nano-Cd particles, we observed that 520Q and 580Q treatment altered the BEAS-2B proteome significantly in a very similar magnitude while 730Q has no obvious impact at all, as compared with the untreated control. Notably, the treatment of BEAS-2B with glutathione before nano-Cd particles abrogated the induction/repression of differentially expressed proteins and prevented cell death. Taken together, our findings show that uncapped CdTe nanoparticles (520Q and 580Q) induce oxidative stress in human bronchial epithelial cells, and the similarly altered protein signatures also suggest potential mitotoxicity and common cellular and detoxification responses upon exposure of lung cells to these two QDs. On the other hand, 730Q may exert a more noticeable effect after long-term exposure, but not upon transient exposure.